Evidence-based hamstring injury prevention is not adopted by the majority of Champions League or Norwegian Premier League football teams: the nordic hamstring survey - Bahr, R.; Thorborg, K.; Ekstrand, J. (British Journal of Sports Medicine, 2015)
Background The Nordic hamstring (NH) exercise programme was introduced in 2001 and has been shown to reduce the risk of acute hamstring injuries in football by at least 50%. Despite this, the rate of hamstring injuries has not decreased over the past decade in male elite football.